India - Improving Household Food and Nutrition Security : Achievements and the Challenges Ahead, Volume 1. Main Report - World Bank (Washington, DC, 2013)
This report focuses on the performance of, and future challenges for, the Government of India's primary "direct food and nutrition safety nets" or food-based transfer programs designed to alleviate short-term food and nutrition insecurity and improve caring behavior within households. This study focuses on the public food distribution system, the government's buffer stocking operations for foodgrain price stabilization, food for work programs, the mid-day meals program, and the integrated child development support services program. A common denominator of this package of interventions is that they all provide direct food assistance to households to mitigate chronic and/or temporary shortfalls in household food consumption. These programs merit special attention as they form one of the key pillars of the government's food and nutrition security strategy. While there is general agreement that measures that promote economic growth and the development of a strong human resource base would have a stronger and more permanent impact on household food and nutrition security, these food-baed transfer programs nontheless play a critical role in enabling the poor and vulnerable households to alleviate the gap not only in short-term deficiencies in food consumption due to inadequate incomes, but also to ease the constraints to the use of selected health and related nutrition services essential to achieving and maintaining long-term nutritional well-being.